A Room of One's Own? Gender and the voyage immobile in Leïla Sebbar's Voyage en Algéries autour de ma chambre. Issue 1 (April 2018) - Wilson, Sonia
Abstract : This essay investigates the strategies deployed by Leïla Sebbar to negotiate between the sequentiality of the book form on one hand and the overwhelming number of textual fragments, objects and images she has collected in her trips around France on the other. These artefacts function for Sebbar as signs of "Algéries en France". Her desire to make them visually available to the wider public is driven by a deep and longstanding need to "mix" or bring together "Algérie" and "France" in order to mend historical rifts and silences. I argue that the trope of the chambre functions as a means for Sebbar to lend coherence to her display of the fragments she has accumulated. By drawing on two literary representations of the chambre in particular, one of which parodies the eighteenth century récit de voyage and the other of which has long secured its place in the feminist literary canon, Sebbar triangulates the reader's visit to her own " chambre ", making three things clear in the process: firstly, the historical rifts she seeks to mend are underpinned by very precise configurations of gender; secondly, the first book we encounter in our personal history as readers has its own story of participation in the construction of the colonial subject; and thirdly, that our rooms are never really, fully our own.